THE INFLUENCE OF ENGLISH CLUB EXTRACURRICULAR ACTIVITIES ON STUDENT SUCCESS IN ENGLISH LANGUAGE COMPETITION - Annisa Kinanti; Hana Silviana; Marcel Gusti Noverdo; Meilani Luthfiyyah Wijaya; Muchamad Abduh; Nurul Octashifa Wibisono; Ridho Hidayatullah; Sara Alfi Muhammad Dzikry; Selvia Putri; Zahrotul Fadilla; Ferdinansyach, Rio (Aisyah Journal of English Language Teaching (AIJELT), 2023)
This research reveals three discussions, namely how the English Club extracurricular is implemented at SMAN 8 Serang City, how the results achieved in these extracurricular activities are seen in the context of linguistic intelligence, and what are the supporting and inhibiting factors during the running of these extracurricular activities. This research is qualitative research with a phenomenological approach. Data collection methods use observation, interviews, and documentation. Meanwhile, data analysis techniques refer to Miles and Hubermann, namely data reduction, data display (data presentation), and conclusion drawing/verification (drawing conclusions). The results of this research are that the implementation of this extracurricular includes two stages, namely the preparation stage and the process stage. Meanwhile, the results of the development of students' linguistic intelligence through the English Club extracurricular activities include listening skills, speaking skills, writing skills, and reading skills. The supporting factors are the strong role of the principal, the professional quality of teachers, good student interest and intelligence, and tools or media that are easy to obtain. Meanwhile, inhibiting factors include this activity not being mandatory material, lack of interest in tutoring at home, and learning media that has not been updated. Keyword: English Club, Linguistic Intelligence, SMAN 8 Serang City